Językowy wyraz świadomości aksjologicznej wspólnoty komunikatywnej warunkowanej prawnie (na podstawie materiałów wstępnych do zbiorów prawa z XVI w.) = The linguistic expression of the axiological awareness of the Polish legally conditioned (on the basis of preliminary materials for the 16th century legal collections) communicative community - Jurewicz-Nowak, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article are linguistic manifestations of the axiological consciousness of the communicative community determined legally in the 16th century. The aim of the publication is to determine what values activated and directed the action of the community (an attempt to present the typology of value names) and how the leading representatives of this community expressed values.
Keywords: wartość; wartościowanie; świadomość aksjologiczna; wspólnota komunikatywna warunkowana prawnie; dyskurs prawny; 16 w.; values; valuation; axiological awareness; legally conditioned communicative community; legal discourse; 16th century